Oriented core application in texture analysis of J1 formation in Kazan oil-gas condensate field (Tomsk Oblast) - Krasnoshchokova, Lubov Afanasievna; Cherdansteva, D.; Yurkova, M.; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
The paper describes the results of the characteristic structure features of oil-bearing rocks via paleomagnetic oriented cores. Volume core model is plotted on the basis of circular panoramic images. In applying scanned panoramic core it is possible to determine the azimuth of terrigenous material transportation and its course and to describe its sedimentation environment in details.
Keywords: нефтегазоконденсатные месторождения; Томская область; нефтеносные породы; скважины; образование; осадочные